Factors Influencing Adeno-Associated Virus-Mediated Gene Transfer to Human Cystic Fibrosis Airway Epithelial Cells: Comparison with Adenovirus Vectors - Teramoto, S. (American Society for Microbiology, 1998)
Adeno-associated virus (AAV) vectors appear promising for use in gene therapy in cystic fibrosis (CF) patients, yet many features of AAV-mediated gene transfer to airway epithelial cells are not well understood. We compared the transduction efficiencies of AAV vectors and adenovirus (Ad) vectors in immortalized cell lines from CF patients and in nasal epithelial primary cultures from normal humans and CF patients. Similar dose-dependent relationships between the vector multiplicities of infection and the efficiencies of lacZ gene transfer were observed. However, levels of transduction for both Ad and recombinant AAV (rAAV) were significantly lower in the airway epithelial cell than in the control cell lines HeLa and HEK 293. Transduction efficiencies differed among cultured epithelial cell types, with poorly differentiated cells transducing more efficiently than well-differentiated cells. A time-dependent increase in gene expression was observed after infection for both vectors. For Ad, but not for AAV, this increase was dependent on prolonged incubation of cells with the vector. Furthermore, for rAAV (but not for rAd), the delay in maximal transduction could be abrogated by wild-type Ad helper infection. Thus, although helper virus is not required for maximal transduction, it increases the kinetics by which this is achieved. Expression of Ad E4 open reading frame 6 or addition of either hydroxyurea or camptothecin resulted in increased AAV transduction, as previously demonstrated for nonairway cells (albeit to lower final levels), suggesting that second-strand synthesis may not be the sole cause of inefficient transduction. Finally, the efficiency of AAV-mediated ex vivo gene transfer to lung cells was similar to that previously described for Ad vectors in that transduction was limited to regions of epithelial injury and preferentially targeted basal-like cells. These studies address the primary factors influencing rAAV infection of human airway cells and should impact successful gene delivery in CF patients.